Xanthine oxidase inhibitory, antioxidant activity and total phenolic content of Momordica charantia L. fruit extracts prepared using two water temperatures / Nurshazwani Wajiha Zainal Rashid and Salfarina Ramli - Zainal Rashid, Nurshazwani Wajiha; Ramli, Salfarina (Faculty of Pharmacy, 2020)
Momordica charantia L. fruit has good reputation for pharmacology and nutrition. Among the reported biological activities include antihyperlipidemic, blood glucose and serum uric acid reducing potentials. In most studies, M. charantia fruit extract was prepared in organic solvents. Nevertheless, water has been a good solvent to extract beneficial compounds with biological activities. Moreover, M. charantia fruit has also being consumed in the form of juice. In this study, the aqueous extracts of M. charantia fruit were prepared by blending the fruits in two different water temperature (25°C and 100°C). After the extracts were lyophilized, the xanthine oxidase inhibitory (XOI), antioxidant activity and total phenolic content of both extracts, along with allopurinol and ibuprofen were measured. From the results, both extracts exhibit XOI and antioxidant activity. The total phenolic content, XOI and antioxidant activity of the 25C and 100C extracts are not significantly different (p>0.05), which is in accordance with the negative correlation between total phenolic content and the activities of extracts. Interestingly, the XOI activity of both extracts are not significantly different from allopurinol (p>0.05), indicating the extracts effectiveness to inhibit xanthine oxidase enzyme. As a conclusion, it is postulated that the activities and total phenolic content of the M. charantia extracts are not affected by the water temperature.